Determinantes do disclosure das práticas de gestão ambiental de empresas listadas na BM&FBOVESPA - Leme, Natalia Carvalho (Universidade do Vale do Rio dos Sinos, 2017)
The present study aimed to identify and analyze the determinants of the disclosure of environmental management practices of companies listed on BM&FBOVESPA. To goals this objective, it was analyzed the Standardized Financial Statements and the Sustainability Reports available on the official website of the Securities and Exchange Commission of Brazil for the years 2013, 2014 and 2015, totaling 190 (one hundred and ninety) companies. Starting from a qualitative analysis, percentage indices were created for each company, which indicates the environmental management practices evidenced. Thus, such practices were categorized into prevention, assessment failures (internal and external) and external environmental events. Regarding the descriptive analysis of the data, the highest indexes corresponded to the categories of Prevention and External Environmental Events, and it was concluded that the analyzed organizations prioritized the disclosure of more positive environmental information to the image of the institutions. These variables, together with the levels of Corporate Governance, EBTIDA and Potential Polluters, were submitted to regression for panel data. The ordinary least squares (OLS) method was used for the estimation of the equation. The results revealed significant relationships between the dependent variable - environmental disclosure - and most levels of corporate governance; between environmental disclosure and environmental management practices; and, with respect to the independent variables related to the pollutant potential, just those variable of small pollutant potential were identified as negatively significant, while for the other variables the results were not significant.
Keywords: Disclosure ambiental; Gestão ambiental; Demonstrações contábeis; Relatórios de sustentabilidade; Environmental disclosure; Environmental management; Accounting statements; Sustainability reports; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis